G336(P) Management of oesophageal coins: a PERUKI study. (May 2019) - Mullen, N; Lafferty, M; Lyttle, M
Abstract : Aims: The majority of ingested coins pass through a child's alimentary tract without causing harm. However if they become lodged in the oesophagus they can cause significant complications. Nonetheless there are no standardised guidelines for the initial management of oesophageal coins in the Paediatric Emergency Department (PED). This study aimed to establish the variation in practice in the management of oesophageal coins in PEDs across the UK and Ireland. Methods: Between 19/03/2018 and 03/05/2018 we conducted an online survey via Paediatric Emergency Research in the UK and Ireland (PERUKI), an international PEM research collaborative. One participant was invited from each site; participants were asked to complete the survey and to submit their local guideline where available. Results are presented using descriptive statistics. Results: 55/61 (90%) sites responded. Coins in the upper 1/3 of the oesophagus: 43/55 (78.2%) referred for endoscopic removal, 6/55 (10.9%) observed and re-assessed, 3/55 (5.5%) referred for surgical opinion, 1/55 (1.8%) removed via Foley catheter, 2/55 were managed according to clinical discretion. Coins in the middle 1/3 of the oesophagus: 33/55 (60%) referred for endoscopic removal; 11 (20%) observed and re-assessed; 2 (3.6%) fed and reassessed; 2/55 (3.6%) referred for surgical opinion; 1/55 (1.8%) removed via Foley catheter; 6/55 (10.9%) were managed according to clinical discretion. Coins in the lower 1/3 of the oesophagus: 19/55 (34.5%) referred for endoscopic removal; 20 (41.8%) observed and re-assessed; 2/55 (3.6%) fed and reassessed; 2/55 (3.6%) referred for surgical opinion; 1/55 (1.8%) gave 'fizzy drink' and re-assessed; 11/55 (20%) were managed according to clinical discretion. Treatments at clinicians' discretion included 'banana and cola', glucagon and use of a nasogastric tube to advance a coin into the stomach. The majority of observations were for up to 4 hours. In approximately 1/3 of observations children were allowed home for the period of observation. Conclusion: There is considerable variation in practice in the management of oesophageal coins in children. A significant minority of PEDs adopt a 'watch and wait' approach while others refer promptly for endoscopic removal. Further investigation is required to determine the optimum initial management.